Histopathological features of thrombotic microangiopathies in renal biopsies - Neto, Miguel Ernandes [UNESP]; Soler, Lucas de Moraes [UNESP]; Vasconcelos, Halita Vieira Gallindo [UNESP]; Dos Santos, Daniela Cristina [UNESP]; Viero, Rosa Marlene [UNESP]; de Andrade, Luís Gustavo Modelli [UNESP] (Maad Rayan Publishing Company, 2019)
Background: Thrombotic microangiopathy (TMA) is a morphologic lesion characterized by thrombi occluding microvasculature related to endothelial injury. Objectives: This study aimed to assess the association between histopathological findings and etiology of TMA. Patients and Methods: This cross-sectional study comprised a sample of 34 patients who underwent renal biopsy and received an initial TMA diagnoses resulting in 29 definitive TMA cases. We evaluated the TMA features and clinical histopathological correlation. Results: The most frequent etiologies were atypical hemolytic uremic syndrome (aHUS) (n= 10; 34.5%), hemolytic uremic syndrome caused by Shiga toxin-producing Escherichia coli (STEC-HUS) (n=6; 24.1%) and secondary causes of TMA (n= 12; 41.4%). We found the following histological features; patients with aHUS had thrombi in 60% of biopsies, membranoproliferative glomerulonephritis (MPGN)-like pattern in 20% and ischemia in 20%; patients with STEC-HUS had thrombi (14.3%), MPGN-like pattern (14.3%), endothelial swelling (14.3%) and ischemia (57.1%); patients with secondary etiologies had thrombi (58.3%), endothelial swelling (16.7%), ischemia (16.7%) and MPGN-like pattern (8.3%). Conclusions: The distribution of classic TMA findings was not related to etiology in spite of micro-thrombi having been found mostly in aHUS and secondary etiologies, whereas ischemia was found mainly in STEC-HUS. We did not find a histopathological pattern to each etiology of TMA.
Keywords: Endothelium; Hemolytic uremic syndrome; Microthrombi; Shiga toxin; Thrombotic microangiopathy